PENGARUH TENAGA KERJA, TEKNOLOGI, DAN MODAL DALAM MENINGKATKAN PRODUKSI DI INDUSTRI PENGOLAHAN GARAM KABUPATEN PATI - S,Pd, Winarsih; M.Si, Baedhowi; Ak, Bandi (Jurnal Pendidikan Insan Mandiri, 2015)
The objective of this research is to investigate whether there is an effect of manpower, technology, and capital on the salt production improvement at salt processing industry of Pati regency. This research used the descriptive quantitative research method. The population of the research 58 persons in Pati regency. The samples consisted of 40 entrepreneurs. The data used were primary data, whick were collected through questionnaire. They study uses multiple regression analys. The results of the research the t test shows that the significance value is 0.005, meaning that the variables of manpower, technology, and capital partially have a significant effect on the salt production. The F test shows the significance value of 0.000 is smaller than that of the significance value of t test = 0.005, indicating that the variables of manpower, technology, and capital have a significant effect on the salt production. The value of R2 is 0.645 meaning that 64.5% of the salt production variations can be verified by the independent variables (manpower, technology, and capital), and the rest 35.4% are verified by other variables outside the regression model. Based on the results of the research it can be concluded that manpower, technology, and capital have a simultaneously significant effect on the salt production improvement at salt processing industry of Pati regency. In order to improve salt production it is suggested that the producers of salt should pay attention to the iodized salt quality in accordance with the SNI standards; and be manpower guidance and training as well as appropriate technology use at the salt industries shall be conducted. Keywords: Manpower, technology, capital and salt production